STUDY OF FACTORS AFFECTING MASTERY QURAN AMONG STUDENTS AT PAHANG STATE COMMUNITY COLLEGE - Zulkefly bin Mukhtar; Norazimah binti Mukhtar (Dinasti International Journal of Education Management And Social Science, 2022)
Al-Quran is a revelation and a guidebook for every Muslim. Therefore, it is an obligation for every Muslim to learn and master the Qur'an so that it can be a guide for life. Highlights from previous studies show many factors that affect students' ability to learn the Quran. Therefore, this study was conducted to find out the factors that influence students' mastery of the Quran from the perspective of themselves, parents, teachers, friends and places of study. This study focuses on Muslim students at Pahang State Community College only, which involves 200 respondents. The study was conducted using quantitative methods. The data collection process is through a questionnaire instrument using a Likert scale. The data was analyzed using IBM SPSS version 22. The results of the study showed that the mean score for oneself was high (mean=4.13), while that for parents was also high (mean=4.22). The mean score for teachers is at a high level (mean=4.22), while the score for friends is at a moderately high score (mean=3.67). The mean score for the place of study is also high (mean=4.26). The results of the study can be refined and improved in future studies and can be made in the form of interviews to obtain more accurate results.